Complications and Resource Utilization Associated With Mechanical Ventilation in a Medical Intensive Care Unit in 2013. (February 2017) - Selvan, Kavitha; Edriss, Hawa; Sigler, Mark; Nugent, Kenneth M.
Introduction: Evolving strategies for ventilator management could reduce the frequency of complications, but there is limited information about complications in contemporary intensive care units. Methods: We retrospectively collected information about patient demographics, chest x-ray abnormalities, complications, including pneumothoraces, ventilator-associated events, self-extubation, and resource utilization in 174 patients who required mechanical ventilation in 2013. Results: The mean age was 57.8 ± 16.8 years, the number of ventilator days was 7.5 ± 7, and the overall in-hospital mortality was 32.2%. The mean fluid balance per day during the mechanical ventilation period was 1539 ± 1721 mL. Three (1.7%) patients developed pneumothoraces, and 5 patients required chest tubes. Twenty-five (14.4%) patients had ventilator-associated events. Ten patients had episodes of self-extubation, and 11 had episodes of failed extubation. Chest X-rays showed new or increasing infiltrates in 113 (64.9%) patients and new or increasing pleural effusions in 29 (16.7%) patients. These patients had 1.2 ± 0.4 X-rays per day on the ventilator, and they had 10.0 ± 9.4 arterial blood gases and 0.7 ± 0.7 central lines. Conclusion: The frequency of ventilator-associated complications was low in this study. However, these patients frequently developed increasing infiltrates, and these outcomes need attention during patient management and are a potential focus for future studies.